The Influence Of Social Media Marketing On Purchase Decisions With The Role Of Brand Image Mediation In The Internet Service Industry Remains First Media - Muchammad Ulil Amri; Yudi Nur Supriadi; Alfatih S Manggabarani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The development of digital technology has driven changes in consumer behavior in accessing internet services and making purchase decisions. In the fixed internet service industry in Indonesia, there are indications of a mismatch between brand image and consumer purchase decisions, especially in First Media. This study aims to analyze the influence of Social Media Marketing on Purchase Decisions with Brand Image as a mediating variable. This study used a quantitative approach with 125 respondents selected through purposive sampling techniques and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The results of the study show that Social Media Marketing has a significant effect on Brand Image (T-Statistic = 8,936; P-Value = 0.000) and Purchase Decision (T-Statistic = 2.283; P-Value = 0.022). Brand Image also has a significant effect on Purchase Decisions (T-Statistic = 5.275; P-Value = 0.000). In addition, Brand Image has been shown to mediate the influence of Social Media Marketing on Purchase Decisions (T-Statistic = 4,203; P-Value = 0.000), which indicates the presence of partial mediation. These findings indicate that effective social media marketing not only directly affects purchasing decisions, but also indirectly through strengthening brand image.